US Policy Toward China During the Presidencies of Donald Trump and Joe Biden: Continuation or Rupture? (Economic and Political Thought, 2023)
Undoubtedly, already during Barack Obama’s presidency, Asia, includingChina, became a key point of the US foreign policy, and the so-called “Pivotto Asia” was a great proof for that. However, while Obama still seemed totreat China as a strategic partner, not seeing it as an existential threat, Trumpdecisively changed this approach and gave a new direction to the Americanstrategy towards China – from then on, China officially became a “strategicrival” and the goal was to slow down its growth in the key areas thatthreatened US security and its global hegemony. The author puts forwardthe thesis that Joe Biden mostly continues Trump’s decisive course towardsChina. Analyzing and comparing official documents of the US government(the American Defence Strategy of 2020 and 2022 and two key documents/speeches presenting the US approach to China during the administrationsof Donald Trump and Joe Biden), the author comes to the conclusion thatthe current president not only continues the course of his predecessor, butalso strengthens it in a few selected areas, such as high technologies and rareearths. The author also attempts to explain the reasons for the followingcontinuation in the US approach to China.
Keywords: US, US foreign policy, Pivot to Asia, Joe Biden, Donald Trump, China, US Security Strategy